Comparative high availability load balancing / Kamarul Ariffin Amin - Amin, Kamarul Ariffin (2015)
Nowadays, web servers are commonly used in multiple large companies. A good server should come with the high-end technological concept in order to maintain the workload and also support the constant application of the particular server. The server must be able to be used in multiple heavy workloads and reliable. In other word, it ensures full optimization, in which the web server will be based to another server that has been connected with other machine. There will be multiple issues with the web server, database server and firewall. The main concern for web server sessions is that they have limited connectivity base scaling, latency, bandwidth and disconnected operation. This issue will be referred as part of the purposes in doing this research project and become proof for the high availability load balancing concept. The problem of load balancing is usually caused by many factors. High availability load balancing should be used in web server base. The purpose of this project will focus more on analyzing the webserver performance and how to resolve a high load bandwidth in the web base by do comparative load balancer method. Nginx will provide high performance and small memory footprint in the web server, as it improving the low performance, less effective and fewer throughputs, the actual objectives of the research are highlighted. The first objective will be to analyze the current performance of web server by do the comparative study of load balancer method, The second one is to resolve the issue of high load bandwidth by using 3 type of method and do the comparative for which method is better for be use. The methodology for this project is RAD methodology, from the result and finding is show each type of load balancer method there have their own special for some purpose be use at, its depend on the environment that require the load balancer. This project the idea is to assist any web server by using load balancer by reducing the conjunction of data bandwidth and overload data transfer.